2023
DOI: 10.1177/10298649231184920
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individual vulnerabilities and problematic behaviors hindering musicians’ development: Obsessive–compulsive personality disorder versus study addiction

Paweł A Atroszko,
Aleksandra Buźniak,
Natalia Woropay-Hordziejewicz
et al.

Abstract: Individual vulnerabilities, such as particular personality characteristics, may be important risk factors that can hinder the development of young musicians and affect their professional careers. This study aimed to examine the relationship between obsessive–compulsive personality disorder (OCPD) and rigid perfectionism, study addiction, and well-being among music students. It was hypothesized that OCPD is a strong risk factor for addictive studying; compulsive learning, however, is an addictive disorder with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…First, study addiction was recently found to be a universal phenomenon in different cultures across the world (Atroszko et al, 2023b). More and more data support the hypothesis that it is an addictive disorder (Atroszko et al, 2023a), and it is more prevalent than most other addictive behaviours, such as video gaming, pornography consumption, food intake, social networking or shopping (Charzyńska et al, 2021; for a detailed analysis of prevalence rates, see Atroszko et al, 2021). It is highly stable in time when unaddressed with any prevention or intervention solutions (Atroszko et al, 2016b), and it may develop into work addiction (Atroszko et al, 2016a), which is likely associated with considerable individual, social, and economic harms and costs .…”
Section: Figurementioning
confidence: 83%
“…First, study addiction was recently found to be a universal phenomenon in different cultures across the world (Atroszko et al, 2023b). More and more data support the hypothesis that it is an addictive disorder (Atroszko et al, 2023a), and it is more prevalent than most other addictive behaviours, such as video gaming, pornography consumption, food intake, social networking or shopping (Charzyńska et al, 2021; for a detailed analysis of prevalence rates, see Atroszko et al, 2021). It is highly stable in time when unaddressed with any prevention or intervention solutions (Atroszko et al, 2016b), and it may develop into work addiction (Atroszko et al, 2016a), which is likely associated with considerable individual, social, and economic harms and costs .…”
Section: Figurementioning
confidence: 83%